(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This essay deals with the linguocognitive analysis of Uzbek and English linguistic units that represent litota. In order to discriminate, Litota sharpens the meaning of words and phrases by lessening their indicators. Litota is referred to as the "reverse hyperbola" because it is the opposite of hyperbola in this respect. Litota is often used for moral reasons: it is possible to develop a favorable impression of something by being humble and downplaying one’s accomplishments.